Unveiling Cultural Beliefs and Perceptions towards Early Breast Cancer Detection and Treatment among Indigenous Penan Women in Sarawak, Malaysia: A Qualitative Study - Rekaya, Vincent Balang; Fitri Suraya, Mohamad; Juriah, Sulehan; Yew, Keh Li; Yong, Zai Yang; Zulkifli, Jantan; Melissa Lim, Siaw Han (RSIS International, 2026)
Background: Early detection of breast cancer plays a critical role in reducing morbidity and mortality. However, uptake of screening practices remains uneven across many rural communities in Sarawak, contributing to late diagnoses and widening the disparities in access to timely treatment. Objective: This descriptive qualitative study explores how cultural beliefs, social norms, and personal perceptions shape women's attitudes and behaviours toward early breast cancer detection with a focused lens on the Penan, an Indigenous minority group in Sarawak. Methods: In-depth semi-structured interviews were conducted with women aged 18–60 in a rural area of Sarawak to elicit their lived experiences, health beliefs, and decision-making processes regarding selfexamination, clinical screening, and seeking medical consultation. Results: Thematic analysis revealed five overarching themes: (1) Trust, Experience, and Accessibility: Determinants of Willingness to Undergo Clinical Breast Examination; (2) Cultural interpretations of breast cancer; (3) Fear and stigma influencing breast cancer screening behaviour; (4) Logistical refrain for seeking medical treatment and breast cancer screening; and (5) Factors Influencing Future Willingness for Clinical Breast Examination. These cultural and perceptual factors collectively influence screening behaviours, often creating barriers despite awareness of breast cancer risks. Conclusion: The findings highlight the need for culturally responsive health communication strategies and community-engaged interventions that address sociocultural concerns while empowering women to participate confidently in early detection practices.